Mobile App Technology Adoption in Indonesia’s Agricultural Sector. An Analysis of Empirical View From Public R&D Agency - Rendi Febrianda (STI Policy and Management Journal, 2021)
Adoption of digital technologies are expected to transform current agricultural system towards sustainability. Mobile application (app) designed to assist farmers decision making has started to revolutionize the agriculture sector of Indonesia. The app offer solutions to farmers by providing information of season prediction, cropping pattern, recommended fertilizers and varieties and so on. This paper aims to review a framework related to diffusion and adoption of digital farming technologies that integrating farm level evidence then compare it with local data based on the empirical view of public agricultural R&D agency. The result indicates that the framework could be the basis for application to foster the adoption of digital technologies where the highlight provides important aspects of the adoption process. The findings also provide what matters more or less. However, limitations remain and future research is needed to improve the understanding.Keywords: Digital technologies, mobile application, adoption, agriculture sector